Researching with care. Attitude change towards epistemic and ontological extractivism as ways of sustaining lives - Sebastiani, Luca; Álvarez Veinguer, Aurora (Cuadernos de Relaciones Laborales, 2024)
In this article, we discuss epistemic extractivism starting from its origin, analysing its multiple meanings and linking it to colonial logics that hinder the sustaining of life. We propose “researching with care” as an alternative to epistemic and ontological extractivism – an alternative that is committed to lives, processes, and people. We present four specific aspects of epistemic extractivism and possible alternatives. Based on our experience, we analyse the tensions encountered and our attempts to research with care. We recommend an attitude change based on caring which affects the materiality of research processes. Facing competence and individuality, we suggest a “situated” and “embodied” research methodology that reflects on “who extracts to whom? Why? For whom?”, we focus on timing – placing people’s lives at the centre – and emphasize the importance of deploying research pieces that are grounded in the territories we live in.